Honour thyself - Steel, Danielle (London : Corgi Books, 2009)
Carole Barber has come to Paris to work on her novel and to find herself after a lifetime in the spotlight. But as her taxi speeds into a tunnel just past the Louvre, a fiery instant of terror shatters hundreds of lives and leaves Carole alone, unconscious and unidentified in a Paris emergency room.
Keywords: Amnesia -- Fiction; Love stories